Дар великой любви, или Я не умею прощать: [роман] / Марина Крамер - Крамер Марина (Королева преступных страстей, 2016)
Экземпляры: ф.14 (20161116) / Инвентарный номер: 52659 / Цена: 90.00 / Авт.знак: К 78 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44